1995
DOI: 10.1002/macp.1995.021960907
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes induced by thermal treatments on emptied and filled clathrates of syndiotactic polystyrene

Abstract: The solvent molecules included in the clathrates (&form) of syndiotactic polystyrene (s-PS) are removed by suitable extraction procedures. An emptied &-form is produced which is different from the known y-form obtained by heating. The structural changes induced by thermal treatments on emptied and filled clathrates of s-PS, have been followed by thermogravimetry, X-ray diffraction analysis, differential scanning calorimetry and Fourier-transform infrared spectroscopy. It is shown that, under suitable condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
239
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(254 citation statements)
references
References 29 publications
(2 reference statements)
14
239
1
Order By: Relevance
“…It is worth noting that a nanoporous structure in these crystals can be prepared by removing the incorporated solvent in acetone or supercritical carbon dioxide (scCO2). [21][22][23][24][25] Similar molecular structures have been reported for syndiotactic poly(p-methylstyrene) (sPPMS); the all-trans conformation (forms III, IV, and V) induced by annealing, and the ttgg conformation (forms I and II) induced by organic solvents. [26][27][28] In addition, three clathrate forms of -, -, and -classes which contain solvent in the crystal unit have been reported.…”
Section: Introductionsupporting
confidence: 64%
“…It is worth noting that a nanoporous structure in these crystals can be prepared by removing the incorporated solvent in acetone or supercritical carbon dioxide (scCO2). [21][22][23][24][25] Similar molecular structures have been reported for syndiotactic poly(p-methylstyrene) (sPPMS); the all-trans conformation (forms III, IV, and V) induced by annealing, and the ttgg conformation (forms I and II) induced by organic solvents. [26][27][28] In addition, three clathrate forms of -, -, and -classes which contain solvent in the crystal unit have been reported.…”
Section: Introductionsupporting
confidence: 64%
“…19 The remaining crystalline modifications, c and d, produced by crystallization from solution, exhibit a helicoidal chain conformation with an identity period of 0.77 nm. 3 Additionally, two mesomorphic phases have been observed, with a helical conformation 20,21 and with a zigzag conformation. 22,23 Guerra et al 3 showed that its complex polymorphism depends on a combination of concurrent factors, such as the cooling rate, the parent's previous initial crystalline form before melting, the maximum temperature (T max ), and the residence time in the molten state.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] There are many studies of d-sPS because solvent molecules can be excluded from the unit cell by soaking in acetone or treating in supercritical CO 2 , without destroying the crystal. [16][17][18][19] It is worth noting that the nanoporous structure of the crystal is maintained, with the solvent-free form denoted d empty -sPS (d e -sPS). 20,21 The pore size has been reported to be 115 Å´3.…”
Section: Introductionmentioning
confidence: 99%